2014
DOI: 10.5194/hess-18-4825-2014
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological dynamics of water sources in a Mediterranean lagoon

Abstract: Abstract. Lagoons are important ecosystems occupying large coastal areas worldwide. Lagoons contain various mixtures of marine and freshwater sources which are highly dynamic in time. However, it often remains a challenge to identify and quantify dynamic changes of water sources, particularly in heterogeneous lagoon systems like the Köycegiz-Dalyan lagoon (KDL), which is located at the south-west of Turkey on the Mediterranean Sea coast. The objective of this study was to quantify different contributions of po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 17 publications
3
11
0
Order By: Relevance
“…Although all studies show a similar trend, the data reported by IMTA (1992) registered heavier δ 18 O values that may be attributable to evaporation or hydrothermal influence. Similar δ 18 O values in thermal systems have been reported in other studies, e.g., El-Fiky (2009) and Stumpp et al (2014), with δ 18 O values ranging from −6.7 to −5.6 and −4.8 to +0.8 ‰, respectively. Hydrothermal groundwater collected in Toluquilla, has a narrow range of δ 18 O (−9.4 to −8.8 ‰) and δ 2 H (−67 to −68 ‰) values.…”
Section: Isotope Hydrologysupporting
confidence: 72%
See 1 more Smart Citation
“…Although all studies show a similar trend, the data reported by IMTA (1992) registered heavier δ 18 O values that may be attributable to evaporation or hydrothermal influence. Similar δ 18 O values in thermal systems have been reported in other studies, e.g., El-Fiky (2009) and Stumpp et al (2014), with δ 18 O values ranging from −6.7 to −5.6 and −4.8 to +0.8 ‰, respectively. Hydrothermal groundwater collected in Toluquilla, has a narrow range of δ 18 O (−9.4 to −8.8 ‰) and δ 2 H (−67 to −68 ‰) values.…”
Section: Isotope Hydrologysupporting
confidence: 72%
“…The combination of different environmental tracer techniques helps elucidate the groundwater's origin, recharge, flow velocity and direction, residence or travel times, connections between aquifers, and surface and groundwater interrelations (Edmunds and Smedley, 2000;De Vries and Simmers, 2002;Appelo and Postma, 2005;Ako et al, 2013;Stumpp et al, 2014). These techniques have been applied in large semiarid to arid rift systems (Bretzler et al, 2011;Furi et al, 2011;Ghiglieri et al, 2012;Siebert et al, 2012;Panno et al, 2013;Forrest et al, 2013;Williams et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Atemajac and Toluquilla valleys consist of a relatively thin cover of Quaternary lacustrine deposits overlying a thick section of Neogene volcanic rocks including silicic domes, lava and cinder cones, lithic tuffs, basalts, ignimbrites and other pyroclastic rocks, andesites and volcanic breccia, and a basement consisting of Oligocene granite (Gutiérrez-Negrín, 1988;Urrutia et al, 2000;Campos-Enríquez et al, 2005) ( Fig. 2).…”
Section: Hydrogeological Settingsmentioning
confidence: 99%
“…The combination of different environmental tracer techniques helps elucidate the groundwater's origin, recharge, flow velocity and direction, residence or travel times, connections between aquifers, and surface and groundwater interrelations (Edmunds and Smedley, 2000;De Vries and Simmers, 2002;Appelo and Postma, 2005;Ako et al, 2013;Stumpp et al, 2014). These techniques have been applied in large semiarid to arid rift systems (Bretzler et al, 2011;Furi et al, 2011;Ghiglieri et al, 2012;Siebert et al, 2012;Panno et al, 2013;Forrest et al, 2013;Williams et al, 2013).…”
mentioning
confidence: 99%
“…Many studies were performed about water quality (Ekdal, 2008;Özçelik, 2015), dynamics (Bayarı, Kurttaş, & Tezcan, 2001;Gönenç, et al, 2004;Stumpp, Ekdal, Gönenç, & Maloszewski, 2014) and biodiversity (Kazancı, Oğuzkurt, Girgin., & Dügel, 2003;Akın, Buhan, Winemiller, & Yılmaz, 2005;Balık, Ustaoğlu, Sarı, İlhan, & Topkara, 2005;Saygılı, Yiğit, & Bulut, 2011) of Köyceğiz Lagoon. However, limited studies on fishes inhabited the ecosystem and fishing practised, are available.…”
Section: Introductionmentioning
confidence: 99%